(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Pet’ko L. V. University foreign language education in the context of the formation of a new teacher. The author examines the modern approaches to the understanding and developing of foreign language education of future teachers in the university training. The article describes necessity of forming of a new teacher, who will be a modern personality, in the process of foreign language teaching in professional way of the students of higher educational establishments.